Review of the secret committees deal with old beliver’s schism in the reign of the Emperor Alexander I - Serebrjakova Julija (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article discusses a history of secret committees deal with measures against old believer’s schism. The author studied archival documents possible to consider confessional politics of the Emperor Alexander I as a new stage of struggle with the old believer’s schism. The first secret committee was established by order of Emperor Alexander I in 1820. This committee was a unique phenomenon in the history of the secret committees of the 19th century and the first experience ofjoint efforts of Church and State against.